2014
DOI: 10.1111/josh.12139
|View full text |Cite
|
Sign up to set email alerts
|

Sugar‐Sweetened Beverage Consumption Among a Subset of Canadian Youth

Abstract: BACKGROUND: Sugar-sweetened beverages (SSBs) may play a role in increased rates of obesity. This study examined patterns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
5
16
0
2
Order By: Relevance
“…In our study, salty snacks and sweetened carbonated drinks were consumed more frequently by boys. Similar results, indicating higher intake of these products among boys, were also demonstrated by Vanderlee et al and Wuenstel et al [26,27].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, salty snacks and sweetened carbonated drinks were consumed more frequently by boys. Similar results, indicating higher intake of these products among boys, were also demonstrated by Vanderlee et al and Wuenstel et al [26,27].…”
Section: Discussionsupporting
confidence: 88%
“…As in another study, we observed no association between weight‐loss or weight maintenance goal and fast‐food consumption, but girls and boys trying to gain weight were more likely to eat fast‐food 3 times per week or more. Other studies have also shown an association between trying to lose weight and lower sugar‐sweetened beverages consumption . Thus, our study also showed that trying to gain weight was associated with higher sugar‐sweetened beverage consumption.…”
Section: Discussionsupporting
confidence: 84%
“…non-diet) soft drinks, fruit drinks, sports drinks, energy drinks, flavoured milk drinks and sweetened coffees/teas. Recent studies demonstrate that youth consume more SSB than any other age group in Canada (1) and many youth consume SSB daily (2)(3)(4) . SSB are a major source of added sugars and energy in adolescents' diets and often have negligible nutritional value (5) .…”
mentioning
confidence: 99%